Easy yoga - Selectmedia Entertainment (Firm).; OverDrive, Inc. (San Francisco, Calif. Selectmedia Entertainment, 2005)
Discover a timeless path to physical and spiritual health, fitness and wellness. For centuries, people all over the world have practiced s system of mind and body exercise called Yoga. This interactive DVD presents the ancient practice of Yoga as s modern way of thinking and living that brings order and balance to busy lives. Our trained yoga expert will take you through a series of positions that can build your body's strength and flexibility, while bringing you toward inner peace and harmony. Just relax and follow along!
VHS ; Color, full-frame, stereo sound, NTSC
English.
Keywords: Hatha yoga; Yoga; Stretching exercises; Instructional videos